Squawk! how to stop making noise and start getting results - Bradberry, Travis (Tantor Audio, 2008)
Unfortunately, we've all been there. You and your team are facing a problem. Yet rather than working with you to come up with a solution, your manager swoops in squawking like a seagull, dumps orders riddled with formulaic advice, then takes off, leaving everyone else to clean up the mess. Or-let's be honest-there's been a time (or two) when all of us have been guilty of this very behavior. The truth is, seagull managers live in every workplace-but it doesn't have to be that way. In Squawk! Travis Bradberry, Ph. D., reveals the three virtues that will help listeners deal with seagull managers in the workplace and, more important, avoid becoming seagulls themselves. Told through the story of Charlie, a well-intentioned seagull manager who doesn't understand how his actions hold back his flock, this entertaining and illuminating fable will help make us all less prone to depositing messes on the heads of those around us.
Keywords: Communication in management; Organizational effectiveness; Communication en gestion; Efficacité organisationnelle; Downloadable audio books; Audiobooks; Livres audio